2010
DOI: 10.1002/jor.21236
|View full text |Cite
|
Sign up to set email alerts
|

Hip screw migration testing: First results for hip screws and helical blades utilizing a new oscillating test method

Abstract: Despite continued improvement in the methods and devices used to treat intertrochanteric fractures, there remains an unacceptable amount of failures. The cut-out rate for hip screws has been recorded up to 8.3%. To evaluate the migration of different implants under physiological loads, a multiplanar biomechanical test method for hip screws was developed, the first to incorporate a simulation of the human gait cycle by an oscillating flexion/extension movement of the test device. The new method was used to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 23 publications
1
57
0
1
Order By: Relevance
“…12 In addition, their mainly axial migration can lead to complications such as cut-through and reverse migration. [13][14][15] As of yet, clinical meta-analyses have not been able to confirm the superiority of either extra-or intramedullary implants. 2,16,17 However, in trochanteric fracture fixation, the cutout rate seems to be related to the design of the device.…”
Section: Introductionmentioning
confidence: 91%
“…12 In addition, their mainly axial migration can lead to complications such as cut-through and reverse migration. [13][14][15] As of yet, clinical meta-analyses have not been able to confirm the superiority of either extra-or intramedullary implants. 2,16,17 However, in trochanteric fracture fixation, the cutout rate seems to be related to the design of the device.…”
Section: Introductionmentioning
confidence: 91%
“…1 However, Born et al 2 reported that the cut-out rate can be as high as 8% for hip screws. Furthermore, cutout of the lag screw from the femoral head is the most common failure mode of fracture fixation with the SHS since it accounts for 80% of implant failures.…”
mentioning
confidence: 99%
“…According to Sommers et al, the onset of migration in the femoral head can be interpreted as the initial stage of cut-out [40]. Based on a threshold of 0.5 mm for a relevant tendency to migrate [29], both implants in our study showed these movements in an axial direction starting at 1200 N. Born et al reported migration of blades in an axial direction and of screws in a cranial direction and ascribed screws a higher resistance to migration [41]. Contrary to their results, migration of the PCCP and the IT in our study can be described as multidirectional with significantly more migration of the IT in an axial direction at the failure point (Fig.…”
Section: Dynamic Stability Coefficientsmentioning
confidence: 89%
“…However, there are varying set ups described in the literature which hampers comparability. There is also considerable variation regarding cyclic loading which ranges from 1 cycle to up to 100,000 cycles per load step [24,25,30,40,41]. The number of cycles per load step in our study resembles the daily step count of a patient in a six weeks rehabilitation program [7,44].…”
Section: Limitationsmentioning
confidence: 93%